(3ef Jhaj YfgG RhLgG aCXgQJ GdZehe hHGMJ HGdecJhes - (3eMeO Hf Nda Hf GdeQRHGf GdeMhdj, GHf GdeQRHGf , CHh HcQ,J (B309 (3g` s ((3CMeO Hf YHO Gddg Hf CHj GdZfGFe s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdUGdM GdRGgO GdeSfO CHh GdMSf Ydi Hf CHj YHO Gddg Hf CHj GdMSf Hf GdebjQ GdHZOGOi bQGAI Ydjg hGfG CSeY ai YTjI LeYI MGOi YTQ TgQ QHjY GdBNQ YGe CQHY hKdGKjf hSJeGFI HLGeY OeTb s
(3BNQgG (B:s
(3adeG aQZJ ef GdTYQ TgbJ aeGJ BNQg hddg GdMeO hGdefI s
(3Ydi dhMI GdYfhGf hbajI hai BNQ GdfSNI SeGYGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B285s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs